1975
DOI: 10.1063/1.321521
|View full text |Cite
|
Sign up to set email alerts
|

CuInS2 thin films: Preparation and properties

Abstract: The growth and electrical properties of CuInS2 thin films are described. Two deposition schemes, single- and double-source methods, are reported. Data are presented indicating the effects of film and substrate temperature on the electrical characteristics (mobility, resistivity, and carrier concentration) of the films. Both n- and p-type films are reported, and the effects of sulfur concentrations are discussed. Some postdeposition annealing effects are also detailed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
26
0
3

Year Published

1978
1978
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(30 citation statements)
references
References 21 publications
1
26
0
3
Order By: Relevance
“…During Hall measurements, it was observed that all films are P-type. It was also observed that a decrease in carrier concentration with increasing substrate temperature ultimately results in an increase in Hall mobility [23,24,25] in the films. This may be explained as being due to the increase in substrate temperature of the films increases the grain size as shown in figure 2.…”
Section: Resultsmentioning
confidence: 90%
“…During Hall measurements, it was observed that all films are P-type. It was also observed that a decrease in carrier concentration with increasing substrate temperature ultimately results in an increase in Hall mobility [23,24,25] in the films. This may be explained as being due to the increase in substrate temperature of the films increases the grain size as shown in figure 2.…”
Section: Resultsmentioning
confidence: 90%
“…There are also various techniques for the preparation of CuInS 2 thin films, such as evaporation [6], chemical vapor deposition (CVD) [7], sputtering [8], molecular beam epitaxy (MBE) [9] and spray pyrolysis [10]. Recently, several morphologies of CuInS 2 have been prepared, such as nanorods [11,12], nanotubes [13], nanoparticles [14,15], foam-like [16] and sphere-like CuInS 2 nanocrystallites [17].…”
mentioning
confidence: 99%
“…There are also various techniques for the preparation of CuInS 2 thin films, such as evaporation [6], chemical vapor deposition (CVD) [7], sputtering [8], molecular beam epitaxy (MBE) [9] and spray pyrolysis [10]. Recently, several morphologies of CuInS 2 have been prepared, such as nanorods [11,12], nanotubes [13], nanoparticles [14,15], foamlike [16] and sphere-like CuInS 2 nanocrystallites [17].…”
mentioning
confidence: 99%